Commentaries on the consumer protection act,1986 - Malik, S. (Allahabad, 1998)
It is a social developing Legislation placed on the Statute Book in 1986 to protect the interest of consumer of goods and services rendered From the working of the Act, it was found necessary to amend the Act and it was thus radically amended in 1993 Under the Act every person who has purchased goods or availed of services is not a consumer for the purposes of the C. P. Act because this Act gives statutory definition of the word "Consumer" Likewise it is only those "goods" or "services" which fall within the purview of the definitions of the word "goods" and "services" that can be the subject matter of a complaint filed under the C. P. Act. Again it is not each and every grievance of a consumer of goods or services that can be entertained under the Act and redressed by the agencies constituted under the C. P. Act because the C. P. Act also gives the definition of the word "Complaint" which enumerates the criteria for determining as to the type of grievances which car be made the subject of a complaint for their redressal Lastly the Consumer Disputes Redressal Agencies constituted under the C. P. Act can not redress the grievances of a consumer in any manner they like or choose because the Act lays down specific remedia orders that can be passed by the Agencies. In nutshel every complaint filed and every order passed, unde the C. P. Act must satisfy the conditions laid down in the various provisions thereof.
Keywords: Consumer protection act- India 1998